The Essence of The Teaching Process in Basic Financial Sciences - Choosing the Right Curriculum Content as The Key to Success - Milena BERA; Wojciech LEWICKI (Communications of International Proceedings, 2024)
The following paper is of a didactic nature and is aimed at both students and teachers to provide basic knowledge and information about education in the field of public finance. The paper discusses in detail the scope of financial management (including local government) and defines the essence of public financial management. At the same time, it indicates which content area should be included in the programme and what factors determined their selection.  The content of the considerations is based on the experience of the presenters from the actual teaching process. The main task of the paper is to facilitate the understanding of the subject in the area of public finance by discussing the range of issues that should be included in the content of such a subject in order to support the learning processes of today's young people. The conclusions of the work can be used in both didactic and scientific work to improve teaching processes.
Keywords: learning environments; financial learning. public finance; education; learning process.